Pancreatoduodenectomía laparoscópica híbrida: resultado en paciente obeso con adenocarcinoma duodenal - Reaño, Gustavo (2023)
Minimally invasive pancreatic surgery has expanded slowly but steadily. The application of this approach in obese patients and/or with periampullary neoplasms is still controversial because of the high complication rate in this group of patients. We present the case of a 62-year-old male, obese (BMI 35.4 Kg/m2), hypertensive and diabetic, who developed severe anemia (Hb 4.9 g/dl) due to duodenal adenocarcinoma. Imaging staging verified localized disease. The patient underwent Hybrid Pancreatoduodenectomy (laparoscopic resection/open minilaparotomy reconstruction). The operative technique and postoperative course are described. The patient had no major complications (moderate acute pancreatitis), the operative time was 540 minutes, the bleeding volume was 400 ml, he required transfusion of 1 unit of globular package and a stay of 8 days. He had no intercurrences during 90 days after surgery. It is concluded that hybrid pancreatoduodenectomy is a feasible and safe alternative in obese patients with duodenal adenocarcinoma, offering advantages in reducing surgical trauma.